Chemical-physical characteristics of buffalo (Bubalus bubalis) meat subjected to different aging times - Luz, Patrícia Aparecida Cardoso Da [UNESP] (2017)
The aim of this study was to evaluate the effects of different aging times on the meat characteristics from young Murrah buffaloes slaughtered at 20-24 months of age (experiment I; n=10) and Murrah buffalo heifers slaughtered at 32-36 months of age (experiment II; n=10), with the purpose of determining the best aging time to tenderize meat from both experiments. Samples of the longissimus thoracis muscle from buffaloes slaughtered at each age were aged for 7, 14, and 21 days (0±1°C). After this period, analysis of cholesterol, pH, cooking loss, shear force, myofibrillar fragmentation index, meat color, and fatty acid profile was performed. Aging greatly improved the tenderness (p < 0.05) but caused a change in color (p < 0.05), which, even without difference between the treatments for subjective perception of the color (ΔE; p > 0.05), was considered very noticeable to the human eye. Furthermore, aging reduced the polyunsaturated fatty acids (p <0.05) and did not affect the levels of cholesterol (p > 0.05) in the meat of young buffalo and buffalo heifers of advanced age. Based on the evaluated meat characteristics, concludes that seven days of aging are sufficient for older buffalo heifers, but 21 days of aging are required for the younger male group.